Nanowire Waveguides and Lasers: Advances and Opportunities in Photonic Circuits - Gu, Zhiyuan; Song, Qinghai; Xiao, Shumin (Frontiers in Chemistry, 2021)
Due to their single-crystalline structures, comparatively large aspect ratios, tight optical confinement and smooth surface, nanowires have retracted increasingly research interests for both fundamental studies and technological applications in on-chip photonic devices. This class of nanostructures typically have cross-section of 2~200 nm and lengths upwards of several micrometers, allowing for the bridging of the nanoscopic and macroscopic world. Especially, the lasing behaviors can be established from nanowire resonator with positive feedback via end-facet reflection, making the nanowire a promising candidate in the next generation of optoelectronics. Consequently, versatile nanowire-based devices ranging from nanoscale coherent lasers, optical sensors, waveguides, optical switching, and photonic networks have been proposed and experimentally demonstrated in the past decade. In this article, significant progresses in the nanowire fabrication, lasers, circuits, and devices are reviewed. First, we focus on the achievements of nanowire synthesis and introduce the basics of nanowires optics. Following the cavity configurations and mode categories, then the different light sources consisted of nanowires are presented. Next, we review the recent progress and current status of functional nanowire devices. Finally, we offer our perspective of nanowires regarding their challenges and future opportunities in photonic circuits.